PREOPERATIVE CARDIAC REHABILITATION IN A 28 YEARS-OLD WOMAN WITH VALVULAR HEART DISEASE - Sri Hastuti Barata; Erna Setiawati; Endang Ambarwati (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Valvular heart disease (VHD) is one third of all heart disease. In industrialized countries, the prevalence is estimated at 2,5% and in developing countries is between twenty to thirty cases per-1000 people. VHD presents a huge health burden worldwide. If heart failure has occured, surgery is the treatment of choice. Cardiorespiratory fitness declined in post-surgical patients. Preoperative cardiac rehabilitation is considered to be able to increase the cardiorespiratory fitness baseline so that postoperative outcomes are better.Case Presentation: We reported 28 years-old female with severe MS and MR as well as mild TR with symptoms dyspnea on effort which improves with rest. She was the candidate for mitral valve replacement. She was given a 14-days preoperative cardiac rehabilitation program including breathing exercise by pursed lips breathing, effective cough exercise, range of motion exercise, ankle pumping exercise, endurance exercise based on the result of the 6 minutes walking test (6MWT) and inspiratory muscle training (IMT) using threshold IMT. Conclusion: Preoperative cardiac rehabilitation program improved pulmonary functional capacity, cardiorespiratory fitness and functional activity.Keyword: valvular heart disease, cardiac rehabilitation, pulmonary functional capacity, cardiorespiratory fitness.